Cutaneous leiomyosarcoma: dermal and subcutaneous. (14th June 2020) - Wong, Gwyneth Natalie; Webb, Angela; Gyorki, David; McCormack, Chris; Tran, Phillip; Ngan, Samuel Y.; Slavin, John; Henderson, Michael A.
Abstract: Background and objectives: Leiomyosarcoma of skin (LMS) can be sub‐classified on pathology appearances as Dermal or Subcutaneous. The aim of this study was to provide treatment recommendations for these uncommon tumours. Methods: A retrospective review of all patients with dermal and subcutaneous leiomyosarcoma managed at the Peter MacCallum Cancer Centre, Australia from January 2003 to December 2018 was performed. Eighty‐three patients were identified (64 dermal leiomyosarcoma, 19 subcutaneous leiomyosarcoma). Results: Subcutaneous leiomyosarcoma were larger (median size 14 mm dermal, 49 mm subcutaneous, P = 0.01). No patient with a dermal leiomyosarcoma developed metastatic disease compared to 4 of the 19 subcutaneous leiomyosarcoma (5‐year overall survivals, 98% and 88%, respectively, P = 0.03). The most common site of metastasis was to the lung. No difference in risk of local recurrence was apparent (5‐year recurrence‐free survivals were 85% and 78%, respectively, P = 0.17). Adjuvant radiotherapy was used in 16 (25%) dermal leiomyosarcoma patients and 13 (68%) subcutaneous leiomyosarcoma patients ( P < 0.001). Local recurrence was uncommon in both tumour subtypes when patients received definitive surgical excision (minimum histological margins of 10 mm as per institutional protocol) regardless of whether radiotherapy was used. The 5‐year local recurrence‐free survival for dermal leiomyosarcoma treated with radiotherapy was 93% versus 83% without radiotherapy ( P = 0.7) and for subcutaneous leiomyosarcoma was 69% and 100%, respectively ( P = 0.9). Conclusions: Dermal leiomyosarcoma have an excellent prognosis, particularly after definitive surgical excision with margins of at least 10 mm. Subcutaneous leiomyosarcoma has poorer outcomes and should be managed by wider excision and considered for adjuvant radiotherapy.